A novel digital control scheme for power management in a hybrid energy-source environment pertaining to electric vehicle applications - Mathesh, G.; Saravanakumar, R. (Frontiers in Energy Research, 2023)
In an electric vehicle (EV), the utilization of different power-sources have invoked to integrate them. This integration inevitably questions the effectiveness of an appropriate power management system (PMS). The integration of sources cause complexity in power conversion, programming errors while switching between the sources and difficulties in real-time implementation. This paper gives a novel digital control scheme specific to the integration of solar, battery and fuel cell to solve these issues and also briefs about PMS in different controllers employed for EVs. The proposed scheme checks out the reference currents based on the power generated by the different sources needed by the instantaneous demand from the permanent magnet synchronous machine (PMSM), which is widely used in EVs. The methodology constitutes maximum power point tracking (MPPT) in solar panels at every second of the day, retaining constant voltage in the DC bus, and managing the power flow from sources to PMSM based on the power availability from different sources. The power flow to a control module dedicated to PMSM control is considered. The major contribution of the paper is the design and development of PMS for an EV with a novel digitl control scheme. Power management is achieved with the aid of a digital controller using real-time solar data for a periodically fluctuating load demand in MATLAB/Simulink and also in an experimental investigation, the results of which are discussed.